Family history of frontotemporal lobar degeneration in Asia – an international multi-center research. (December 2014) - Fukuhara, Ryuji; Ghosh, Amitabha; Fuh, Jong-Ling; Dominguez, Jacqueline; Ong, Paulus Anam; Dutt, Aparna; Liu, Yi-Chien; Tanaka, Hibiki; Ikeda, Manabu; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Previous studies in western countries have shown that about 30%–50% of patients with frontotemporal lobar degeneration (FTLD) have a positive family history, whereas the few epidemiological studies on FTLD done in Asia reported much lower frequencies. It is not clear the reason why the frequencies of FTLD with positive family history were lower in Asia. Furthermore, these findings were not from studies focused on family history. Therefore, it is necessary to conduct further studies on the family history of FTLD in Asia. This international multi-center research aims to investigate the family histories in patients with FTLD and related neurodegenerative diseases such as progressive supranuclear palsy (PSP), corticobasal syndrome (CBS), and motor neuron diseases in a larger Asian cohort. Methods: Participants were collected from five countries: India, Indonesia, Japan, Taiwan, and Philippines. All patients were diagnosed with behavioral variant frontotemporal dementia (bvFTD), semantic dementia (SD), progressive non-fluent aphasia (PA), frontotemporal dementia with motor neuron disease (FTD/MND), PSP, and corticobasal degeneration (CBD) according to international consensus criteria. Family histories of FTLD and related neurodegenerative diseases were investigated in each patient. Results: Ninety-one patients were included in this study. Forty-two patients were diagnosed to have bvFTD, two patients had FTD/MND, 22 had SD, 15 had PA, one had PA/CBS, five had CBS and four patients had PSP. Family history of any FTLD spectrum disorder was reported in 9.5% in bvFTD patients but in none of the SD or PA. Conclusion: In contrast to patients of the western countries, few Asian FTLD patients have positive family histories of dementia.